Repositioning Wives’ Roles in Urban Households: Social Support, Dual Burdens, and the Negotiation of Family Resilience - Sagita, Insharie Amarylis; Maulidia, Rohmah; Santoso, Lukman (Islamic Family Law Study Program, Sharia Faculty, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The changing times have brought significant changes to the role of women in the family and society, where increased access to education and gender equality have encouraged women's contribution to the workforce and family economic welfare. However, the dual roles carried out by career women often result in a double burden due to the demands of the public and domestic spheres, making family resilience an important issue that needs to be further researched. This study aims to explore the social support received by wives as career women for family resilience, as well as strategies for negotiating role sharing in social institutions at the family level. This study uses a qualitative field approach with ethnographic techniques, in which the researcher conducts participatory observation and in-depth interviews with informants. The theories used are legal anthropology theory, role theory, power theory, and family resilience theory. The results show that wives as career women receive social support from the public sphere, such as coworkers and workplace policies, as well as from the domestic sphere, such as their immediate family and parents. This support includes help with housework, childcare, and fulfilling the wife's needs, which are very important in maintaining a balance between dual roles. The division of roles within the family is influenced by the length of marriage, number of children, working hours, and place of residence. Effective role negotiation strategies include open communication, agreement, task flexibility, family deliberation, and mutual respect. The success of maintaining family resilience is largely determined by the ability to adapt and negotiate roles, which is influenced not only by practical needs, but also by the dynamics of power, cultural values, economics, and legal frameworks that complement each other.